Resveratrol modulates intestinal morphology and HSP70/90, NF-κB and EGF expression in the jejunal mucosa of black-boned chickens on exposure to circular heat stress. Issue 3 (4th February 2016) - Liu, Lili; Fu, Chenxing; Yan, Mingli; Xie, Hongbing; Li, Si; Yu, Qifang; He, Shaoping; He, Jianhua
Abstract : The aim of this study was to investigate whether supplementation with resveratrol could alleviate intestinal injuries and to explore how resveratrol regulates heat shock protein (HSP)70, HSP90, nuclear factor kappa B (NF-κB) and epidermal growth factor (EGF) expression in the jejunal mucosa of black-boned chickens under circular heat stress. Abstract : The aim of this study was to investigate whether supplementation with resveratrol could alleviate intestinal injuries and to explore how resveratrol regulates heat shock protein (HSP)70, HSP90, nuclear factor kappa B (NF-κB) and epidermal growth factor (EGF) expression in the jejunal mucosa of black-boned chickens under circular heat stress. A total of 300 black-boned chicks of 42-d-old were randomly assigned to five treatment groups. The positive control chickens were kept in a normal-temperature (NT, 24 ± 2 °C) chamber and fed with a basal diet. The other four groups were kept in a circular high-temperature (HT, 37 ± 2 °C) chamber for 8 h and fed a basal diet supplemented with 0, 200, 400, or 600 mg per kg of resveratrol for 15 days. The results showed that the heat-stress responses damaged the villus structures of the jejunum and ileum, resulting in shortened intestinal villi, deepened crypts, and a reduced villus height to crypt depth (V/C) ratio and decreased the numbers of goblet cells and lymphocytes. Heat stress also caused increased mRNA and protein expression of HSP70, HSP90 and NF-κB, and reduced EGF in the jejunal mucosa. Dietary supplementation with 400 mg per kg of resveratrol improved the villus morphology, increased the numbers of goblet cells and lymphocytes, attenuated the mRNA overexpression of HSP 70, HSP 90 and NF-κB on the 6 th, 10 th and 15 th day of heat stress ( P < 0.05), and activated the expression of EGF ( P < 0.05) in the jejunal mucosa. Resveratrol reduced protein expression of HSP70, HSP90 and NF-κB in the jejunal villi after 15 days of heat stress, and increased EGF expression from the lamina propria toward the epithelial cells of the villi. These results suggest that dietary resveratrol offers a potential nutritional strategy to improve the intestinal morphology and alleviate jejunum mucosa injuries by modulating the mRNA and protein expression of HSPs, and the epithelial growth factor and transcription factor in black-boned chickens subjected to circular heat stress.